Genetic polymorphism of adult reindeer coat colour in a herding cooperative in Finnish Lapland - Lauvergne, Jean J.; Nieminen, Mauri (Rangifer, 2011)
In a random sample of 188 adult reindeer belonging to a reindeer herding cooperative in Finnish Lapland, the following coat colour mutants were identified: Abf at the locus Agouti (A), kalppinokka (WNk) at the locus White Nose (WN) and white at the locus W (White). Coefficients of coat colour phenotypic polymorphism K were estimated, in order to quantify this genetic polymorphism. Estimations of K were 12.8% for the locus A (Agouti), 5.1% for the locus WN (White Nose), and 7.5% for the locus W (White). This polymorphism results probably from a change in fitness coefficient of genotypes carrying colour mutants following domestication in a random mating context which has not yet been proved.